1995
DOI: 10.1002/app.1995.070571308
|View full text |Cite
|
Sign up to set email alerts
|

New measures of polydispersity from rheological data on polymer melts

Abstract: SYNOPSISThe rheological properties of polymer melts depend strongly on the underlying molecular structure: molecular weight, molecular weight distribution, and long chain branching. It is of considerable importance, both fundamental and practical, to relate the molecular architecture to polymer melt rheology. The focus of the present work is in extracting a measure of polydispersity from rheological data. Various polydispersity measures that have been proposed in the literature are critically examined and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 22 publications
1
64
0
1
Order By: Relevance
“…[7] When the LCB content is very low (less than 1 LCB /10 4 C), its effect on the radius of gyration goes unnoticed and values of g ≈ 1 are obtained [42]. The effect of such a low amount of LCB has been explored in LDPE and in modified linear polymers of ethylene/α-olefins and propylene (PP) by irradiation, electron-beam treatment, peroxide reaction, and thermal/mechanical degradation [7,10,17,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In principle, lowpressure processes (chromium-based and Ziegler-Natta type catalysts, developed in the 1950s and 1970s, respectively) yield linear species.…”
Section: Conventional Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…[7] When the LCB content is very low (less than 1 LCB /10 4 C), its effect on the radius of gyration goes unnoticed and values of g ≈ 1 are obtained [42]. The effect of such a low amount of LCB has been explored in LDPE and in modified linear polymers of ethylene/α-olefins and propylene (PP) by irradiation, electron-beam treatment, peroxide reaction, and thermal/mechanical degradation [7,10,17,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In principle, lowpressure processes (chromium-based and Ziegler-Natta type catalysts, developed in the 1950s and 1970s, respectively) yield linear species.…”
Section: Conventional Polymersmentioning
confidence: 99%
“…Shroff and Mavridis [142] stated that DRI is a measure of rheological polydispersity and as such depends on both MWD and LCB. DRI could be used as a measure of LCB for polymers of known similar MWD, as could any other measure of rheological polydispersity [54]. …”
Section: Relaxation Time and Steady-state Compliancementioning
confidence: 99%
See 2 more Smart Citations
“…In general, it has been concluded that CRPP resins have lower molecular weight, narrower MWD and reduced viscosity. In addition, it has become clear that one of the most significant challenges for the polymer processing engineer is the problem of inter-conversion between rheological data and the MWD (Shroff and Mavridis (1995)). …”
Section: Degradation Of Polypropylene (Pp)mentioning
confidence: 99%